2021
DOI: 10.28945/4745
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Influence Physicians' Billing Accuracy?

Abstract: Every year, medical billing errors cost the United States government billions in public funds wrongfully or erroneously paid out. While recent reports indicate modest decline in hospital billing errors, the rate of physician evaluation and management billing errors show no signs of improvement. Opinions vary on the causes of these billing errors and consequently on the appropriate countermeasures. Despite this national crisis, to date, no strategies have proven to improve physician billing accuracy. This resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Similar studies have also indicated that due to the inadequate reflection of labor value caused by the introduction of new policies, medical professionals resort to unexpected behaviors, providing the system with authentic feedback. This feedback is beneficial for the real exposure of problems and facilitates the development of solutions to bring the healthcare system back on track (22)(23)(24). Therefore, we can conclude that unexpected behaviors cannot simply be categorized as negative or positive; they are merely behavioral changes.…”
Section: Qualification Of Unexpected Behaviorsmentioning
confidence: 99%
“…Similar studies have also indicated that due to the inadequate reflection of labor value caused by the introduction of new policies, medical professionals resort to unexpected behaviors, providing the system with authentic feedback. This feedback is beneficial for the real exposure of problems and facilitates the development of solutions to bring the healthcare system back on track (22)(23)(24). Therefore, we can conclude that unexpected behaviors cannot simply be categorized as negative or positive; they are merely behavioral changes.…”
Section: Qualification Of Unexpected Behaviorsmentioning
confidence: 99%